2021
DOI: 10.1111/iju.14616
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with paclitaxel and gemcitabine after platinum‐based chemotherapy in patients with advanced urothelial cancer

Abstract: Abbreviations & Acronyms AE = adverse event BC = bladder cancer CI = confidence interval CTCAE v4.0 = Common Terminology Criteria for Adverse Events version 4.0 GC = gemcitabine and cisplatin GCarbo = gemcitabine and carboplatin GEM = gemcitabine HR = hazard ratio ICI = immune checkpoint inhibitor IQR = interquartile range LN = lymph node MEC = methotrexate, epirubicin and cisplatin MVAC = methotrexate, vinblastine, doxorubicin and cisplatin ORR = objective response rate OS = overall survival PFS = progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…No non-hematologic AE was classified as more than grade 3 in either study, and AEs were, overall, manageable, with no therapy-related death. Moreover, the AE profile in a recent retrospective study, which used almost the same 2nd-line GP regimen as in the present study but on an every-4-weeks schedule, were also in line with ours [ 13 ]. Not only were AEs during 2nd-line GP in the present study tolerable, but GP was also observed to be independently prognostic for PFS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…No non-hematologic AE was classified as more than grade 3 in either study, and AEs were, overall, manageable, with no therapy-related death. Moreover, the AE profile in a recent retrospective study, which used almost the same 2nd-line GP regimen as in the present study but on an every-4-weeks schedule, were also in line with ours [ 13 ]. Not only were AEs during 2nd-line GP in the present study tolerable, but GP was also observed to be independently prognostic for PFS.…”
Section: Discussionsupporting
confidence: 90%
“…The present study, which includes a relatively large cohort compared with other studies of 2nd-line GP for aUC, updates our previous reports about this doublet [ 10 , 11 , 12 , 13 ]. In this cohort, GP was associated with an ORR of 35.8% and a median OS of 12.3 months with a tolerable toxicity profile.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 16 Given that the standard second‐line regimen was not yet defined before 2018 (pre‐pembrolizumab era), some patients were continuously treated with the first‐line therapy beyond PD. Our regimens for salvage chemotherapy included docetaxel‐based regimes (e.g., docetaxel + ifosfamide + nedaplatin or paclitaxel + gemcitabine), 17 , 18 or rechallenge of first‐line therapy.…”
Section: Methodsmentioning
confidence: 99%